Surgical Intervention for Pectoralis Major Muscle Rupture: Report of Acute and Chronic Cases - Erica Kholinne; Cheong-su Lim; Julius I. Kho; In-Ho Jeon (Case Reports in Surgery)
Pectoralis major muscle rupture is becoming more frequent due to the current trends toward high-contact sports. We reported 2 cases with acute and chronic injury settings along with the strategy to treat each of it.